Structure, electronic properties and chemical bonding in bis(1H-imidazolium-KN3)silver(I) nitrate from periodic DFT computations - Stashans, A. (2017)
Using the first-principles density functional theory calculations within the generalized gradient approximation we study the bis(1H-imidazolium- KN3)silver(I) nitrate molecular crystal. A number of different exchange-correlation functionals are considered for a possible treatment of the system. Perdew-Burke-Ernzerhof (PBE) GGA exchange-correlation functionals are found to be adequate for our system. The obtained results show that it is possible to reproduce very well the geometry of at least some molecular crystals if computational parameters are chosen adequately. In addition to the reproducing crystal structure of the bis(1H-imidazolium-KN3)silver(I) nitrate in close agreement with the available experimental data, the present work reports analysis on the chemical bonding in the material and gives total and partial density of states of this system.